Policies of Architectural Conservation in Ancient Places Case study: Historical Citadel of Erbil - HAMED, FARIS SHOKRE; HAMED, ABD AL BAQI ABD AL GABAR (Nahrain University College of Engineering Journal, 2008)
The research aims to determine the suitable policy to preserve the historical Citadel of Erbil basis of the data into three stages through which the morphological (Citadel planning and its construction, urban fabric, and urban land use) trying to answer the following questions: - To what extent the Citadel can be consider as a Frey (eroded)? - To what extent can maintain the existing buildings within the parameters of acceptable planning? - How can we Revival the Citadel within the modern urban fabric of the City that is not at the expense of the Architectural heritage of the Castle? Using the Analytical - Descriptive methodology, reached several Conclusions and Recommendations to avoid errors committed by the former in the Revival of this site and other Historical sites in Iraq.